Reimagining climate futures: Reading Annihilation. Issue 137 (December 2022) - Iossifidis, Miranda Jeanne Marie; Garforth, Lisa
Abstract: In this paper we explore how reading speculative fiction (SF) can be understood as a generative way to participate in a wider reckoning with the idea, and increasingly the experience, of climate crisis. Focusing on Jeff VanderMeer's 2014 novel Annihilation as an example of New Weird fiction, we examine how the uncanny atmospheres brought to life by the text, and the affective responses of some of its readers, create new ways of imagining climate futures. SF critics and other cultural commentators have focused on what novels, authors and genres can do to reconfigure cultural narratives of a climate-changed world, and their impact or effect on the imaginations of readers. But they rarely explore empirically how nonprofessional readers are engaging with speculative climate fiction. Our contribution to assessments of the power of the fictional imagination in the age of the Anthropocene focuses in a detailed and qualitative way on what SF readers can make with SF texts rather than on what texts are said to do to readers. We centre the social and affective experiences of fiction reading and sense-making, and foreground how readers collectively discuss the pleasures of fiction that dwells on these themes and affects. Drawing on Verlie's (2021) work on affective adaptation, we suggest that the medium of SF reading can constitute a rich and generative way to understand and live with climate crisis.